Creating shared views of customers: Individuals as sense-makers in multinational companies - Pernu, Elina; Mainela, Tuija; Puhakka, Vesa (Industrial marketing management, 2015)
Global suppliers' relationships with their global customers tend to be complex, as each consists of multiple geographical, technological and functional units. For a supplier to manage these customer relationships, some shared views of each relationship are likely to be needed for consistency of activities. This creates a need within supplier MNCs to make sense of customers. This research focuses on sense-making by individuals in supplier MNCs. It considers individuals acting in the sense-making process a means of creating shared views. A qualitative process research strategy is utilized to uncover this process. As a result, this research recognizes four mechanisms, defined as individual-level behavioral patterns, for creating shared supplier views of the customer: defining, linking, triggering and creating. Furthermore, the study defines the triggers that cause individuals increasingly to share similar or dissimilar views of the customer. These triggers are recognized at different levels of management: within the MNC (i.e., internal cooperation, shared projects, limited customer contacts), at the customer-relationship level (i.e., previous cooperation with the customer) and at the network level (i.e., involvement of third parties). •Development of customer relationships is driven by individual-level sense-making.•This research focuses on sense-making by individuals in supplier MNCs.•We recognize four mechanisms for creating shared supplier views of the customer.•Shared views are needed for managing and taking care of customer relationships.